Pengaruh Komunikasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Pegadaian Cabang Boswesen Kota Sorong - Intan Karisago (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
This study aims to find out and analyze the influence of work communication on the performance of employees of the Boswesen branch of Sorong city. This study uses a qualitative research method using a survey method through a survey given to Boswesen branch employees of Sorong City with 50 respondents. Data analysis is carried out based on thematic and category questions that reveal emerging trends. Data analysis was carried out using multiple regression analysis. The value of the regression constant of 629 means that if Communication (X1) and Work Discipline (X2) = 0, then the purchase decision has a value of 629 meaning that if the variable price (X1) and location (X2) = 0 = 0, then the purchase decision is worth 629, so without price and location then the purchase decision has a positive value. The regression coefficient X1 for the price variable has a positive value of 0.256, which means that if the price variable increases by 1 unit, then the dependent variable, namely the purchase decision, will also increase by 0.764. The regression coefficient X2 for the location variable has a positive value of 0.60, which means that if the location variable increases by 1 unit, then the dependent variable, namely the purchase decision, will increase by 0.764. The results showed that each price and location variable had a positive and significant effect on the purchase decision, but the price variable had a positive and significant effect on the purchase decision. Simultaneously or simultaneously, product price and location variables have a positive and significant influence on purchasing decisions. The findings of this study may explain why the main research that examined product prices and locations is consistent with purchasing decisions.